Boron addition to AISI A213/P91 steel: Preliminary investigation on microstructural evolution and microhardness at simulated heat‐affected zone. Issue 10 (5th October 2022) - Khajuria, A.; Akhtar, M.; Bedi, R.
Abstract: The motivation behind present investigation has been a step to create preliminary understanding towards structure‐property correlation i. e., microstructure and microhardness in presence of boron in P91 steel and in its subzones of heat‐affected zone with Gleeble simulation. For microstructure characterization and its comparison amongst selected two steels, light microscopy for prior austenite grain size, morphology of prior austenite grain boundaries and scanning electron microscopy at low‐resolution and high‐resolution in order to study evolution of sub‐structure i. e. martensitic lath block structure and nano‐precipitates were employed. Electron backscatter diffraction measurements of all coupons were done to understand the distribution and contribution of relative fraction of various grain and sub‐grain boundaries within local microstructure. Main effects of addition of 100 ppm boron to standard P91 steel as observed from present microstructural evaluation are; existence of fine nano‐precipitates P91‐coarse grained heat affected zone than its P91B counterpart, grain refinement in fine‐grained heat‐affected zone of both steels with partial dissolution of nano‐precipitates, coarsened nano‐precipitates in P91‐fine‐grained heat‐affected zone after post weld heat treatment, mixed‐structure of partially transformed martensite and coarsened undissolved prior austenite grains with nano‐precipitates in P91‐inter‐critical heat‐affected zone than P91B‐inter‐critical heat‐affected zone. However, difference in microhardness was primarily owing to variation of nano‐precipitates fraction area. In addition, present work induced grounds for microstructure stability i. e., grain boundary hardening in P91B weldments that suppresses type IV failure. Abstract : Gleeble simulation of P91 and P91B steels was carried out to obtain various heat‐affected zones i. e., coarse‐grained, fine‐grained, and inter‐critical heat‐affected zone. The novel achievement of this work is development of reasoning on stability of microstructure in P91B weldments from electron backscatter diffraction analysis for improved grain boundary hardening that leads to suppression of type IV failure.